Introduction (Scottish Historical and Archaeological Internet Reports, 2001)
This section presents details of site location and topography. The typical criteria of well-drained, secluded, wooded valleys for Cistercian foundations of the 12th century are well met at Dundrennan. The sharp course of the Abbey Burn also provided suitable areas for cultivation to the east of the main abbey buildings, a further favourable condition for its foundation. The river drained the area of the abbey and adjacent fields, creating the potential for gardens and orchards, although the ground is prone to flooding.